Creativity in the classroom schools of curious delight - Starko, Alane J. (Routledge, 2018)
"Creativity in the Classroom, sixth edition, helps teachers link creativity research and theory to the everyday activities of classroom teaching. This foundational textbook is relevant for any course dealing wholly or partially with creativity and teaching. The sixth edition has been revised and updated throughout, informed by cutting-edge research on neurobiology, curiosity and imaginative play, questioning, and motivation, particularly the relationships among creativity, intrinsic motivation, and motivation to learn"--Provided by publisher.